Correlation between immediated pigmentation with oxydative DNA repair. A study among elementary school children under sun exposured sport activity - Retno Mustikaningsih, Retno Mustikaningsih (Universitas Gadjah Mada, 2005)
Background: Oxydative DNA damage, namely 8-OHdG, may occurred due to DNA oxydation by reactive oxygen species (ROS). Unrepaired 8-OHdG may initiate a carsinogenesis due to G to T transversion of gene point mutations. The 8-OHdG repair can be measured by determination of urinary 8-OHdG level. It is well known that ROS reaction with preexisting melanin may perform an immediate pigmentation darken-ing (IPD) and it can be measured by mexameter. The correlation between IPD and 8-OHdG repair capacity is still not known.Aim of Study: To know the correlation between IPD and 8-OHdG repair ability in order to predict the oxydative DNA repair capacity.Methods: Using of a quasi experimental design, 8-OHdG urine level alteration correlated with skin color alteration after oxydative stress among 30 healthy elementary-school children during sport activity pro-gram under sun exposure. 24 hours of skin color alterations as a IPD were measured by mexameter, and urinary-8- HdG- level were measured based on ELISA with 8-OHdG-Kit antibody. The correlation be-tween IPD and 8-OHdG urine level alteration was analyzed with Spearman test.Results: There was a very significant correlation between immediate pigmented darkening and urinary 8- OHdG level alteration (r=0.8562; p<0.01).Conclusion: IPD represents 8-OHdG repair capacity after oxydative stressed under sun exposure Keyword: immediate pigmention darkening - 8-OHdG -mexameter - sun exposure